2009
DOI: 10.1055/s-0029-1211405
|View full text |Cite
|
Sign up to set email alerts
|

Reinnervation of Pancreatic Islets and Regulation of Insulin Secretion by Hepatic Sympathetic Nerves after Intraportal Transplantation of Islets into Livers of Diabetic Rats

Abstract: It was the aim of this study to elucidate whether intraportally transplanted pancreatic islets were reinnervated after transplantation and whether the secretion of insulin from pancreatic islets might be modulated by the vegetative innervation of recipient livers. Two weeks after intraportal transplantation of 2000 neonatal pancreatic islets recipient rats completely recovered from streptozotocin-induced diabetes. Predominantly catecholaminergic, but also cholinergic nerve fibers were detected in islet cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…43,44 Correlation was shown between the success rate for diabetes reversal and the minimal number of syngeneic islets: 100% reversal with 1000 islets (approximately 3500 islets/ kg), 33% with 700 islets (2500 islets/kg), and 0% with 500 islets (1700 islets/kg). In the 1990s, 2000 syngeneic islets were reported to reverse diabetes in LEW rats.…”
Section: Comparison To Previous Rat Intrahepatic Transplantationsmentioning
confidence: 97%
See 1 more Smart Citation
“…43,44 Correlation was shown between the success rate for diabetes reversal and the minimal number of syngeneic islets: 100% reversal with 1000 islets (approximately 3500 islets/ kg), 33% with 700 islets (2500 islets/kg), and 0% with 500 islets (1700 islets/kg). In the 1990s, 2000 syngeneic islets were reported to reverse diabetes in LEW rats.…”
Section: Comparison To Previous Rat Intrahepatic Transplantationsmentioning
confidence: 97%
“…In the 1990s, 2000 syngeneic islets were reported to reverse diabetes in LEW rats. 43,44 Correlation was shown between the success rate for diabetes reversal and the minimal number of syngeneic islets: 100% reversal with 1000 islets (approximately 3500 islets/ kg), 33% with 700 islets (2500 islets/kg), and 0% with 500 islets (1700 islets/kg). 45 Another study reported 0% reversal with 2500 islets/kg.…”
Section: Comparison To Previous Rat Intrahepatic Transplantationsmentioning
confidence: 97%
“…This is in contrast to some previous experiments where physical exercise induced a decrease in serum insulin concentration from islets implanted into the liver in rats, also after adrenalectomy ( 22,23 ). Also direct stimulation of hepatic nerves in the perfused liver of rats transplanted intraportally with neonatal islets demonstrated an inhibition of insulin release 9 months post-transplantation ( 24 ), presumably through α 2 -adrenoceptors ( 25 ). Islets implanted into the portal vein also exhibit pulsatile insulin secretion, which is likely to be due to reinnervation ( 26-28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, insulin secretion is controlled by the sympathetic and parasympathetic nervous systems. When the sympathetic nerve is stimulated, it releases norepinephrine, which inhibits insulin secretion by inducing vasoconstriction and suppressing β cell function [ 6 ]. In contrast, when the parasympathetic nerve is stimulated, it can promote insulin secretion by releasing acetylcholine, which activates muscarinic receptors in β cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%